CORRELATIONAL STUDY REGARDING THE ATTENTION OF THE PREPARATORY CLASS STUDENTS TO THE PHYSICAL EDUCATION AND SPORT LESSON - Denisa BĂLĂNEAN; Simona PETRACOVSCHI (Cluj University Press, 2021)
Introduction: There are disorders that cannot be observed only with the naked eye and tend to be confused with lack of intelligence, in this category falling attention deficit. Objectives: The study aimed to analyze correlations between the level of attention and gender of children in the preparatory class, to highlight differences between girls and boys, as well as to identify the existence of increased attention of each gender, depending on the time of the lesson physical education and sport. Methods: Two specific tests were used: The Toulouse-Pieron Test (1982) and The Raven Progressive Matrices (1938). After applying the tests, for a period of 2 months, the direct observation method was applied. This study involved 51 children, including 22 girls and 29 boys, from the preparatory class. Results: The link between the level of attention and the gender of the students was demonstrated, at ρ = 0.773, with a significance threshold of .000, which shows the very significant association between the 2 variables. Obtaining a coefficient t = 7.758 and a significance threshold of .000, highlights the existence of a very statistically significant difference between the two groups. There was also a distinct degree of attention between the 2 genres, which fluctuated depending on the activity proposed. Conclusions: Girls have a higher degree of attention than boys, there is a link between the gender of students and the focus on certain tasks; girls are more attentive than boys to moments that involve bodily expression activities, while boys are more attentive than girls to competitive activities. REZUMAT. Studiu corelațional privind atenția elevilor de clasa pregătitoare la lecția de educație fizică și sport. Introducere: Există afecțiuni care nu se pot observa cu ochiul liber și care pot fi confundate cu lipsa de inteligență, în această categorie încadrându-se deficitul de atenție. Obiective: Studiul și-a propus să analizeze corelații între nivelul atenției și genul copiilor din clasa pregătitoare, să evidențieze diferențe între fete și băieți și să identifice existența unei atenții mai sporite a fiecărui gen, în funcție de momentul lecției de educație fizică și sport. Metode: S-au utilizat două probe specifice: Testul Toulouse-Pieron (1982) și The Raven Progressive Matrices (1938). Ulterior aplicării testelor, pe o perioadă de 2 luni s-a aplicat și metoda observației directe. La acest studiu au luat parte 51 de copii, dintre care 22 de fete și 29 de băieți, elevi de clasa pregătitoare. Rezultate: S-a demonstrat legătura dintre nivelul atenției și genul elevilor, la un ρ= 0,773, cu un prag de semnificație de .000, care arată asocierea foarte semnificativă dintre cele 2 variabile. Obținerea unui coeficient t= 7,758 și a unui prag de semnificație de .000, evidențiază existența unei diferențe foarte semnificative statistic între cele două grupuri. S-a observat, de asemenea, un grad distinct de atenție între cele 2, oscilând în funcție de activitatea propusă. Concluzii: Fetele prezintă un grad mai ridicat de atenție decât băieții, existând o legătură între genul elevilor și focusarea pe anumite sarcini; fetele sunt mai atente decât băieții la momentele care cuprind activități de expresie corporală, în timp ce băieții sunt mai atenți decât fetele la activitățile competitive. Cuvinte cheie: deficit de atenție, gen, asociere, concentrare, momentele lecției.